Solusi Praperencanaan Kepemilikan Rumah Bagi Generasi Z dengan menggunakan Pendekatan Design Thinking - Andri Tri Wibowo; Anggara Pernando; Irma T. Handayani; A. Taryana (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study explores the application of the design thinking approach in the pre-planning phase of subsidized homeownership for Generation Z in Indonesia. As Generation Z enters adulthood and begins to plan for the future, they face various challenges in achieving homeownership, particularly regarding financial issues and access to subsidized housing programs. The design thinking approach is used to gain a deeper understanding of the needs, desires, and barriers faced by Generation Z through the stages of empathy, problem definition, ideation, prototyping, and testing. By focusing on innovative and user-centered solutions, this research aims to design a more relevant and acceptable subsidized homeownership model for Generation Z. The findings of this study are expected to provide insights for housing developers and policymakers in designing more efficient and appropriate housing policies and programs that align with the socio-economic dynamics of Generation Z.